2018
DOI: 10.1080/09637486.2018.1511689
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic effect of a phytosterol-ingredient and its main phytosterol (β-sitosterol) in human cancer cell lines

Abstract: Dietary interventions may effectively control cancer development, with phytosterols (PS) being a class of cancer chemopreventive dietary phytochemicals. The present study, for the first time, evaluates the antiproliferative effects of a PS-ingredient used for the enrichment of several foods and its main PS, β-sitosterol, at physiological serum levels, in the most prevalent cancer cells in women (breast (MCF-7), colon (HCT116) and cervical (HeLa)). In all three cell lines, these compounds induced significant ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 36 publications
0
27
0
1
Order By: Relevance
“…However, epidemiological studies have suggested that increased consumption of phytosterols can reduce the risk of different cancers [19, 33, 38, 61]. Data from cancer cell lines have shown that β-sitosterol can reduce cell proliferation and induce apoptosis in addition to inhibiting adhesion, invasion, and migration [2, 46, 8, 50, 64, 65, 70]. β-sitosterol has also been shown to inhibit the growth of tumor xenografts, reduce progression of carcinogen-induced tumors, and prevent metastatic lung and lymph node colonization [5, 8, 28, 29, 54].…”
Section: Discussionmentioning
confidence: 99%
“…However, epidemiological studies have suggested that increased consumption of phytosterols can reduce the risk of different cancers [19, 33, 38, 61]. Data from cancer cell lines have shown that β-sitosterol can reduce cell proliferation and induce apoptosis in addition to inhibiting adhesion, invasion, and migration [2, 46, 8, 50, 64, 65, 70]. β-sitosterol has also been shown to inhibit the growth of tumor xenografts, reduce progression of carcinogen-induced tumors, and prevent metastatic lung and lymph node colonization [5, 8, 28, 29, 54].…”
Section: Discussionmentioning
confidence: 99%
“…144,[181][182][183][184][185][186] β-Sitosterol controls the expression and activity of HPV E6 and p53, which induces the apoptosis and arrests the growth of CC cells. 187,188 Limitations of the current study include the lack of experiments that evaluate the anti-CC effects and toxicity of combined treatment of FDY2004 with other anticancer agents involved in chemotherapy, targeted therapy, and cancer immunotherapy. Further investigations are needed to expand the therapeutic application of herbal drugs as anticancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Gajendran, Durai, Varier, and Chinnasamy [22] reported that Rinoxia B (4 and 10 µM), a phytosterol isolated from leaf extract of Datura inoxia, induces apoptosis via upregulation Bax/Bcl-2 ratio and inhibits cell proliferation through downregulation of cell cycle regulatory proteins (Cyclidin D1 and B1) and G 2 /M arrest in HCT 15 human colon adenocarcinoma cell line. Meanwhile Alvarez-Sala et al [243] indicated that phytosterols (β-sitosterol, sitostanol, campesterol, campestanol, and stigmasterol) from tall oil (13 µM) exert an antiproliferative effect in the breast (MCF-7), colon (HCT116), and cervical (HeLa) cancer cell lines, through the increase of sub-G1 cell population (apoptotic cells).…”
Section: Anti-cancermentioning
confidence: 99%